Development and clinical evaluation of a new sensor design for buccal pulse oximetry in horses. (21st September 2017) - Reiners, J. K.; Rossdeutscher, W.; Hopster, K.; Kästner, S. B. R.
Summary: Background: The use of pulse oximetry in horses is limited due to inadequate readings with conventional transmission sensor probes. Objectives: The objectives of this study were to 1) develop an improved sensor design for horses to be used at an appropriate anatomical site, and 2) evaluate this design in an experimental study. Study design: In vivo experiment. Methods: A new sensor design for reflectance pulse oximetry at the buccal mucosa was developed. A conventional Nonin 2000SL sensor for transmission pulse oximetry was included into this design. Three different prototypes (N1, N2a, N2b) were constructed and used with the Nonin 2500A Vet pulse oximetry monitor. Thirteen anaesthetised warmblood horses were included into a desaturation protocol (100–70% SaO2 ). SpO2 and pulse frequency values were recorded, using SaO2 calculated from blood gas analysis and invasive pulse frequency measurements as reference methods. Bias and precision were evaluated by calculations of the root mean square deviation (Arms ). The agreement of the methods was tested with Bland‐Altman analysis. Results: The quality of the pulse frequency readings determined the quality of the SpO2 ‐readings. Good pulse signal strength resulted in a SpO2 ‐accuracy comparable to that of the original sensor (Nonin 2000SL: Arms = 3%; N1: Arms = 3.60%; N2b: Arms = 3.46%). Especially at heart rates ≤30 bpm, pulse rate readings that were about twice as high as the reference value occurred. Their exclusion from the dataset resulted in a pulse rate accuracy similar to that of the original sensor. Bland‐Altman plots showed limits of agreement typical of pulse oximeters. Main limitations: The pulse frequency accuracy requires further improvement. The usability in clinical cases needs to be tested. Conclusions: The new sensor design has been shown to be suitable for buccal pulse oximetry in horses.